A study of the critical articles contained in the book Letters and Articles (Part Three Literary Radiance) by Sayyid Muhammad al-Sadr () (Journal of the College of Basic Education, 2022)
The history of Arab literature is rich in all kinds of creativity, without any trace of light, effects and images of names that have been shed in the skies of the Arab world in general and Iraq, in particular, to which we bow to reverence and magnificence. We are unable to fulfill their right whenever we want to deal with them in detail and detail. He had a clear footprint in more than one area. He was a man who modified a nation as a whole. He did not limit himself as a man of religion and jurisprudence, as he believed in many, but he saw it was open on every level. He was a brilliant star in the skies of the great leaders who did not limit themselves to the field of jurisprudence Or science or politics, but also to the field of literature He has produced a number of important literary works, including his book (Letters and Essays). He was a brilliant writer in the fields of story, essay, mission, adventure, etc., as well as in the field of poems and poems. And levels. The second study was devoted to the study of the articles in the book of letters and articles (Part III literary breakthroughs) divided into two sections, the first dealt with the definition of articles and types. The second was to analyze the technical and critical of some literary articles (monetary articles mode. (